Likened to “a Boiled Egg”: A New Framework for Understanding Chinese Postgraduate Taught Students’ Transitional Experience - Zhang, JIE; Elliot, Dely Lazarte; Makara, Kara A. (Journal of International Students, 2024)
International students make significant contributions to the UK and Chinese international students represent the largest body of overseas students in the UK. Although previous studies have examined different aspects of this cohort, an in-depth and comprehensive investigation of the experience of Chinese postgraduate taught students is seemingly very limited. This research employed a longitudinal design and conducted 34 interviews with the facilitation of photograph- and diagram-elicitation techniques. With a phenomenological focus, Interpretative Phenomenological Analysis, an inductive approach, was employed for the data analysis of this research investigation. Nine superordinate themes emerged to capture academic, social, linguistic and psychological aspects of students’ experience as well as motivations prior to their experience and expectations subsequent to their journey. This research offers a holistic framework of student experience by illustrating various emerging needs in different layers and highlighting English proficiency and social connections as two influential factors on other elements of student experience.